2019
DOI: 10.1155/2019/3068748
|View full text |Cite
|
Sign up to set email alerts
|

Improving Physical Activity mHealth Interventions: Development of a Computational Model of Self-Efficacy Theory to Define Adaptive Goals for Exercise Promotion

Abstract: The practice of regular physical exercise is a protective factor against noncommunicable diseases and premature mortality. In spite of that, large part of the population does not meet physical activity guidelines and many individuals live a sedentary life. Recent technological progresses and the widespread adoption of mobile technology, such as smartphone and wearables, have opened the way to the development of digital behaviour change interventions targeting physical activity promotion. Such interventions wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…Additionally, participants emphasized their interest in a flexible physical activity app that adapts the intervention content to the specific context and variations in the users' motivational and emotional states in real time. This suggestion is in line with recent emerging research that has focused on the development of just-in-time adaptive interventions [44] and tailoring physical activity interventions on motivational aspects such as self-efficacy beliefs [45,46].…”
Section: Comparison With Prior Worksupporting
confidence: 71%
“…Additionally, participants emphasized their interest in a flexible physical activity app that adapts the intervention content to the specific context and variations in the users' motivational and emotional states in real time. This suggestion is in line with recent emerging research that has focused on the development of just-in-time adaptive interventions [44] and tailoring physical activity interventions on motivational aspects such as self-efficacy beliefs [45,46].…”
Section: Comparison With Prior Worksupporting
confidence: 71%
“…A total of 5 studies were conducted in the United States [ 12 , 92 , 94 - 96 ], 1 in Italy [ 86 ], 1 in New Zealand [ 87 , 88 ], and 1 in the Netherlands [ 89 - 91 ]. Of these, 3 studies used pre-post intervention designs [ 87 , 92 , 95 ], 2 were RCTs [ 94 , 96 ], 1 was a 3-arm quasi-experimental study [ 89 ], 1 was a single-group microrandomized trial [ 12 ], and 1 was development study [ 86 ]. The duration of the studies ranged from 3 weeks to 6 months.…”
Section: Resultsmentioning
confidence: 99%
“…The duration of the studies ranged from 3 weeks to 6 months. A total of 5 studies recruited participants from community settings [ 12 , 86 , 87 , 89 ], 1 from the university campus and community [ 92 ], 2 from the university only [ 94 , 96 ], and 1 from a university wellness center and retiree mailing list [ 95 ]. Populations included insufficiently active and sedentary healthy adults, healthy and highly educated young adults, overweight and sedentary adults, adults with chronic low back pain, and students and staff from a university setting.…”
Section: Resultsmentioning
confidence: 99%
“…Such beliefs are particularly relevant with regard to health-related behaviors [ 50 ]. In the context of CVD, it has been shown that self-efficacy plays a crucial role in adopting and maintaining a healthy diet [ 26 , 51 ] and a physically active lifestyle [ 51 , 52 ]. Especially for maintenance, the confidence in one’s abilities to preserve the newly developed behavior in spite of the possible barriers is pivotal.…”
Section: Discussionmentioning
confidence: 99%